2014
DOI: 10.1002/eji.201444512
|View full text |Cite
|
Sign up to set email alerts
|

c‐Cbl regulates MICA‐ but not ULBP2‐induced NKG2D down‐modulation in human NK cells

Abstract: The NKG2D activating receptor on human NK cells mediates "altered self" recognition, as its ligands (NKG2DLs) are upregulated on target cells in a variety of stress conditions. Evidence collected in the past years shows that, even though expression of NKG2DLs acts as a danger signal that renders tumor cells susceptible to cytotoxicity, chronic exposure to soluble or membrane-bound NKG2DLs can lead to down-modulation of receptor expression and impairment of NKG2D-mediated cell functions. Here, we evaluated whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 55 publications
3
58
0
Order By: Relevance
“…Conjugates were gently re-suspended and spun onto poly-L-lysine-coated glass slides as described previously, 58 incubated for 15 min at 37 °C followed by incubation at 4 °C for 10 min to promote spontaneous adhesion. Cells were fixed (3.7% paraformaldehyde), permeabilized (0.5% saponin), incubated with 0.1 M glycin (Bio-Rad, code 161-0718) followed by blocking buffer (1% FCS, 0.05% saponin) and stained with anti-CD16 followed by Alexa Fluor 488-labeled GAM (Invitrogen) Abs.…”
Section: Methodsmentioning
confidence: 99%
“…Conjugates were gently re-suspended and spun onto poly-L-lysine-coated glass slides as described previously, 58 incubated for 15 min at 37 °C followed by incubation at 4 °C for 10 min to promote spontaneous adhesion. Cells were fixed (3.7% paraformaldehyde), permeabilized (0.5% saponin), incubated with 0.1 M glycin (Bio-Rad, code 161-0718) followed by blocking buffer (1% FCS, 0.05% saponin) and stained with anti-CD16 followed by Alexa Fluor 488-labeled GAM (Invitrogen) Abs.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were analyzed using a FACSCanto (BD Biosciences, San Jose, CA). For microscopy experiments, samples were prepared and visualized using a fluorescence microscope equipped with the ApoTome system, as previously described (27).…”
Section: Immunofluorescence Facs and Microscopic Analysismentioning
confidence: 99%
“…In follow up publications, it was shown that two synergistic activating signals, for example, through NKG2D and CD244 are needed to overcome blockade by c-Cbl (104) and that this synergistic action is mediated by a combined phosphorylation of separate tyrosine residues of the adaptor protein SLP-76 (105). On the other hand, c-Cbl is involved in a kind of negative feedback loop in the down regulation of NKG2D after prolonged exposure to one of its ligands, MICA (106). …”
Section: Cbl-b Function In Nk Cellsmentioning
confidence: 99%